Therapeutic Targeting of TRPV1 by Resiniferatoxin, from Preclinical Studies to Clinical Trials - Kissin, Igor; Szallasi, Arpad (Current Topics in Medicinal Chemistry, 2011)
In primary sensory neurons, the capsaicin receptor TRPV1 functions as a molecular integrator for a broad range of seemingly unrelated chemical and physical noxious stimuli, including heat and altered pH. Indeed, TRPV1 is thought to be a major transducer of the thermal hyperalgesia that follows inflammation and tissue injury as this response is impaired in TRPV1-deficient mice. Following the molecular cloning of TRPV1 in 1997, over a dozen companies embarked on efforts to find clinically useful TRPV1 antagonists, but side-effects and limited efficacy have thus far prevented any compounds from progressing beyond phase II. This has rekindled interest in desensitization of nociceptive neurons to TRPV1 agonists (e.g. capsaicin and its ultrapotent analog resiniferatoxin) as an alternative pharmacological approach to block pain in the periphery where it is generated. The clinical value of capsaicin is, however, limited by its unfavorable irritancy to desensitization ratio. In animal experiments, resiniferatoxin treatment is a powerful approach to achieve longlasting analgesia. In patients with overactive bladder, intravesical resiniferatoxin improves bladder function (or even restores continence) without significant irritancy and/or toxicity. In this review, we argue that resiniferatoxin is an attractive alternative to capsaicin in that it achieves lasting desensitization without the side effects that complicate capsaicin therapy.
Keywords: overactive bladder